La regularización de la contratación de Gamers por parte de los equipos de e-sports profesionales dentro de nuestro Marco Legal Ecuatoriano. - Saigua Puetate, Ángel Paúl (2024)
This research is generated through the need to regulate the new work activities that emerged in our country. In our country, as a result of the pandemic, there is the generation of various ways of working, these new ways generate the emergence of new ways of employing, the formation of professional teams is one of the activities that has had the greatest growth in recent years and this phenomenon brought with it the need to hire professional virtual players, which is a new way of hiring that needs regularization. The legal regulatory framework, specifically in the current Labor Code, establishes a differentiation of contracts, which are the different forms and ways in which one can legally contract in our country, but, when generating a new activity, it is necessary to establish a new way in which which this hiring should be carried out, this in pursuit of the care and protection of workers and their rights. This research will work under different methodologies, the descriptive one, through the implementation of this methodology it seeks to broadly describe the need for regularization of this type of work, explanatory, through which the research work will explain why what is necessary to regulate the contracting of professional digital sports teams and the exploratory research method, through which the needs, in the legal field, that are generated through the appearance of digital sports teams are investigated. In this study, an analysis is made of the need to create a legal figure that regulates the contracting that occurs by professional digital sports teams, since current Ecuadorian legislation does not regulate this type of contracting. Likewise, this research investigates the state of legality of professional digital sports teams existing in our country.